2018
DOI: 10.1134/s0003683818070062
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Debaryomyces hansenii within ORMOSIL Shells as a Heterogeneous Biocatalyst

Abstract: ⎯The relevant sol-gel encapsulation methods to design ORMOSIL (organically modified silica) protective shells around Debaryomyces hansenii yeast cells have been studied. Encapsulation is based on spontaneous "cell-in-shell" 3D structures. The physiological activity of the sol-gel encapsulated cells was determined by measurement of the oxidative activity of a BOD biosensor containing ORMOSIL-encapsulated cells. It was shown that the shells around the microbial cells did not prevent substrate diffusion and had e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Heterogenic electron transfer constant equaling 0.0098 ± 0.0005 cm/s confirms quite a high efficiency of the studied matrix as compared to the matrices based on organic materials and CNT described in Nguyen and Zink (2002)and Ngo et al (2019). Although the received constants are slightly lower than the constants of matrices based on multi-walled CNT and high-oriented polyaniline nanotubes (Ponamoreva et al 2018), generally it may be still suggested that the developed electrodes have high analytical properties.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Heterogenic electron transfer constant equaling 0.0098 ± 0.0005 cm/s confirms quite a high efficiency of the studied matrix as compared to the matrices based on organic materials and CNT described in Nguyen and Zink (2002)and Ngo et al (2019). Although the received constants are slightly lower than the constants of matrices based on multi-walled CNT and high-oriented polyaniline nanotubes (Ponamoreva et al 2018), generally it may be still suggested that the developed electrodes have high analytical properties.…”
supporting
confidence: 51%
“…5) to determine the main characteristics of the electrochemical process. Anodic peak was reached at potential E pa = − 400 mV, cathodic peak at E pc = − 490 mV; difference of peaks (ΔE p ) amounted to 90 mV, which corresponds with the electrochemical behavior of glucose oxidase (Ponamoreva et al 2018). This is suggestive of glucose oxidase coenzyme's (FAD) capability to reduce to FADH 2 and oxidize in such conditions.…”
mentioning
confidence: 81%
“…Organically modified silicates (ORMOSILs) are hybrid silicon xerogels that combine the mechanical, thermal, and structural rigidity and stability of inorganic materials with the flexibility and functionality of organic molecules [ 1 ]. These properties favor their utilization as chemical and optical sensors [ 2 , 3 , 4 , 5 , 6 , 7 ], catalysts [ 8 , 9 ], coatings [ 10 , 11 , 12 , 13 , 14 ], chromatographic agents [ 15 , 16 ], nanoprobes, and photovoltaic cells [ 17 , 18 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…The data in Table S3 (Supplementary Material) for the three chloroalkyl series show that the contribution of the LO 4 band (attributable to the total percentage of (SiO) 4 rings) increases with higher percentage of precursor. This is a relevant finding, given that this band is also associated with the presence of ordered structures in the literature [ 5 , 51 , 65 ]. Its presence is closely related to a decrease in the degree of crosslinking in the xerogel, in agreement with the shifts at lower wavelengths of the TO 4 band, which is associated with the silicon network [ 13 ].…”
Section: Resultsmentioning
confidence: 56%
“…Organically modified silicon xerogels (ORMOSILs) are attracting considerable interest for their application in new-generation technologies, being utilized in chemical and optical sensors [ 1 , 2 , 3 , 4 , 5 , 6 ], for catalysis [ 4 , 5 ], in coatings [ 6 , 7 , 8 , 9 , 10 ], for chromatography [ 11 , 12 ], and in pharmacy [ 13 ]. They have great chemical versatility and can be efficiently modified for specific applications due to their combination of highly varied mechanical, optical and textural properties [ 14 ].…”
Section: Introductionmentioning
confidence: 99%